Regeneration after paraendodontic surgery in tooth with extensive bone fenestration - Case report with 3 years follow-up (Research, Society and Development, 2021)
This clinical case reports bone repair after paraendodontic surgery with the use of mineral trioxide aggregate (MTA) and guided tissue regeneration (GTR). The patient sought the Orthodontics Clinic at Faculdade COESP, showing disocclusion on element 11, grade II mobility. On radiographic examination, an apical radiolucency was observed, from the root of tooth 13 to 11, needing to be referred for endodontics. With a doubtful prognosis, it followed with endodontic retreatment and after 3 months the surgical intervention was performed. Then, the graft was accommodated in the bone store, followed by adaptation of the membrane and suture. After 6 months, there was no sensitivity to vertical percussion and palpation. After 3 years, new bone formation was observed in the periapical region, thus, it was concluded that the chosen method of disinfecting the environment and using a bone graft in addition to guided tissue regeneration promoted a satisfactory bone regeneration with the consequent maintenance of the dental element in the oral cavity.